Identification of Calcium Oxalate in Urine Sediment for Consuming Caffeinated Drinks at Pauwo Village in 2021 - Novendra Puluhulawa; Wiharsri; Rini Daud Supu (Journal of Health, Technology and Science (JHTS), 2022)
This study aimed to determine urinary calcium oxalate sediment in men and women who consume caffeinated drinks in the Pauwo Village, Bone Bolango district in 2021. The method in this study used a qualitative approach with the type of research used was descriptive univariate. The type of data used was primary data and secondary data sourced from questionnaires. The sampling technique in this study used a purposive sampling technique using a sample of 30 people consisting of men and women who consumed caffeinated drinks. The results showed that of the 30 samples of men and women who consumed caffeinated drinks in the Pauwo Village of Bone Bolango district found abnormal urine sediment as many as 21 people from 30 samples and normal urine sediment as many as 9 people from 30 samples which contained calcium oxalate urine sediment in it. The factors that influence the presence of calcium oxalate in men and women include age, gender, and duration of consuming caffeinated drinks.